Pollen, Tapetum, and Orbicule Development in Colletia paradoxa and Discaria americana (Rhamnaceae) - M. Gotelli; B. Galati; D. Medan (The Scientific World Journal)
Tapetum, orbicule, and pollen grain ontogeny in Colletia paradoxa and Discaria americana were studied with transmission electron microscopy (TEM). The ultrastructural changes observed during the different stages of development in the tapetal cells and related to orbicule and pollen grain formation are described. The proorbicules have the appearance of lipid globule, and their formation is related to the endoplasmic reticulum of rough type (ERr). This is the first report on the presence of orbicules in the family Rhamnaceae. Pollen grains are shed at the bicellular stage.